Total quality management and Lean in the logistic process of a company that commercializes LED lighting products - Souilem, Malek (2015)
Nowadays, the globalized economy leads the emergence of highly competitive companies. Many companies are competing not only to keep track and boost their customer’s satisfaction but also to look for other potential resources, to increase their market share regarding other competitors. The companies have to organize their business and internal processes in order to maximize efficiency and therefore achieve their objectives and maintain their growth and expansion in a very struggling economy constrained by austerity. For these reasons, the companies need to manage their industrial production/business process towards reducing the cost while maintaining high quality products or services to maintain and attract more customers. This seems clearly a conflicting situation, however, it is possible for the companies to balance these tradeoffs by implementing the methodologies of continuous quality improvement, waste minimization, and cost reduction simultaneously for their goods or services, through good management approaches of their supply chain, inventory, and quality control process. The objective of this master project is to integrate the total quality and supply chain management methodologies within a Lean thinking framework in order to install a sustainable continuous improvement(Kaizen) process in a company near Aveiro city, the Primelux company. This will be achieved through, firstly identifying the company current working processes and then trying to improve the quality in the overall processes by minimizing the failures in preparing orders and on the after-sales processes as well as through reducing the cost by minimizing the waste using 5S lean tools applied to the LED products logistics in the Company. The work will start by developing qualitative and visual representation of the above-mentioned logistics processes and completed with a quantitative analysis that evaluate the supply chain performance through adequate metrics after applying a set of action plans that were efficiently communicated to the employees by means of an easy and illustrative training. The achieved improvements through this proposed approach that combine the 5S-Kaizen-TQM tools are reported in this report, namely a reduction in failure rate and the time saving in the execution of the logistics process that will have surely a direct impact on the company customer satisfaction.